The Career Development Model of Students of Private Vocational High School Veteran 1 of Tulungagung during the Pandemic - Pratiwi, Niken Hari; nurhadi, didik; Yoto, Yoto (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The online learning system during the pandemic of COVID-19 has changed the system for conselling services in such a way that guidance and counselling teachers at vocational high schools are required to be creative and innovative in performing services for students online. They are shouldering more responsibilities because during the pandemic the rate of employment termination has increased, while that of job vacancies has decreased, which constitutes a serious challenge for students’ career development. They are also faced with the problem of exploring career choices, finding good jobs in accordance with students’ interests and characters, and improving students’ career prospects withouth meeting those students in person. This research focused on knowing the career development model of the students of Private Vocational High School (PVHS) Veteran 1 of Tulungagung during the pandemic. This was qualititative approach with descriptive research in which the data obtained from interviews and observation were presented in a descriptive report which can be easily understood. The research findings shows that guidance and counselling teachers are able to follow technological advances, foster innovation, and establish good communication with industries and business world during the pandemic of COVID-19. Guidance and counselling teachers of PVHS Veteran 1 of Tulungangung continues to provide counselling services for career development by combining online and offline models in a scheduled appoinment by still obeying health protocols.